Transforming Educational Management in Islamic Boarding Schools: A Historical and Digital Perspective - Wawan Shofwani; Iis Arifudin; Ria Yulia Gloria; Djohana Rochanda Wiradinata (Jurnal Pendidikan (Teori dan Praktik), 2025)
This study explores the transformation of educational management in Islamic boarding schools (Islamic Boarding School ) from historical and digital perspectives, using Buntet Islamic Boarding School in Cirebon as a case study. Employing a qualitative-descriptive design with a historical approach, the research integrates literature review, field observation, and semi-structured interviews. The findings reveal three significant transformation dimensions: (1) the digitalization of management systems through applications such as Simapel and SIMATREN, which enhance accountability, transparency, and institutional efficiency; (2) curriculum transformation that integrates classical Islamic texts (kitab kuning) with modern digital pedagogy, improving students' religious and technological literacy; and (3) the strengthening of Islamic Boarding School -based academic culture through research development, publication, and digital literacy training. The study concludes that the managerial transformation of Islamic Boarding School is not merely a response to modernization but an adaptive effort to harmonize spirituality and digital innovation in a hybrid management model. Recommendations include expanding digital literacy programs, training educators in educational technology, and fostering collaboration with external institutions to sustain innovation. This research contributes to the global discourse on Islamic educational management by demonstrating how faith-based schools can balance tradition and technological progress within a culturally grounded framework.